COMPARATIVE ANALYSIS OF THE OWN EXPERIMENTAL TECHNIQUES OF PRODUCING THE FOAMED GLASS-CERAMIC - LUCIAN PĂUNESCU; MARIUS FLORIN DRĂGOESCU; SORIN MIRCEA AXINTE (Journal of Engineering Studies and Research)
The paper presents experimental results obtained by a team of researchers from the company Daily Sourcing & Research SRL Bucharest in the field of producing the foamed glass-ceramic from waste bottle glass, coal ash and silicon carbide as foaming agent. The originality of the experiments consists in the use of electricity or microwave energy, unlike all techniques known worldwide consumers of fossil fuel. The product, obtained with low energy consumptions and very low pollutants emissions, has physical and mechanical characteristics of an insulating material, i.e. high porosity, low thermal conductivity and an adequate compressive strength.